Exploring the Elderly Care System: A View from Community in Thailand - Amaraporn Puraya; Duangporn Piyakong; Sugritta Wongwiggan; Roongtiva Boonpracom (Universitas Airlangga, 2021)
Introduction: Thai society is becoming an aging society due to the increase of the population aged 60 years or above. Developing the elderly care system in the community is important and needs cooperation from many sectors in order to provide care for the elderly effectively.   The objective of this research was to explore the meanings of the elderly care system in community in Thailand, using a qualitative research approach. Methods: This descriptive qualitative research design was conducted with 40 informants at a community in a province located at the lower northern region of Thailand. The informants were divided into two groups. 1) The main informants were the Chief Executive of the Local Administrative Organization (LAO). 2) The secondary informants were those who had been guided to help the elderly in the community and family.  The data were collected by observation, in-depth interviews, focus group discussions and document study. The reliability of the data was verified by triangulation. The data were analyzed by content analysis. Results: The results of  the meanings of the elderly care system in community was defined as five themes: providing help and support, having networks, volunteerism, having knowledge and knowledge management, and community solidarity. Conclusion: The elderly care system in the community is in line with the participation process of all parties, both inside and outside the area, to jointly conduct activities to deal with problems and develop various operations in the area to support the elderly care system in the community.